Development of Learning Outcome Test Instruments on Thermodynamics and Waves Based on The Demands of Basic Competencies - Abdul Haris; Khaeruddin Khaeruddin; Sri Reski (Jurnal Ilmiah Pendidikan Fisika, 2024)
Evaluation is a process of determining the results of a learning activity that has been conducted using instruments. This development research aims to develop test instruments for physics learning outcomes that meet valid and reliable criteria. The tests developed were multiple-choice tests in the form of physics material based on the 2013 curriculum, such as thermodynamics and mechanical waves. This research is a research and developmental project that uses the development method according to Djaali and Mulyono, which generally has seven steps: (1) formulating conceptual and operational definitions, (2) designing instruments, (3) reviewing statements, (4) testing, (5) analysis, (6) revising instruments, and (7) instrument assembly into the final instrument. The study's results were analyzed using Microsoft Excel, analyzing the items' validity, reliability, difficulty level, and differentiability level. Validity using the biserial point coefficient, reliability using Kuder Richardson 20, difficulty level using the simple proportion of correct answers, and differentiability using high groups. The research results indicate that the physics learning outcomes test meets valid and reliable criteria. The valid question items were 33 items, and the reliability of the instrument in the first test was 0.77, and in the second test was 0.81. Teachers can use the developed instrument to assess students' learning outcomes because it remains consistent after testing on the same subjects and conditions.